Influence of Organizational Culture, HR Quality, Discipline, and Motivation on Employee Performance at Kosgoro 1957 Business Institute - Afrijal Afrijal; Isnaini Muharifah; Eka Dea Safitri (Proceeding of The International Conference on Economics and Business, 2023)
This study aims to analyze the factors theoretically considered to have a relationship with job satisfaction of employees at the Institute of Business and Informatics Kosgoro 1957 (IBI-K57). These factors include achievement motivation and organizational culture as independent variables, which are then analyzed for their relationship with job satisfaction of employees at the Institute of Business and Informatics Kosgoro 1957 (IBI-K57) as the dependent variable. The study was conducted over six months, from August 2022 to January 2023. This is a quantitative study employing correlation analysis and regression analysis to measure the relationship between the two independent variables and the dependent variable. The data used are primary data based on the questionnaire responses of the employees/academic community of the Institute of Business and Informatics Kosgoro 1957 (IBI-K57). The population of this study consists of 63 employees within the scope of the Institute of Business and Informatics Kosgoro 1957 (IBI-K57) in South Jakarta. The results of this study can demonstrate the relationship between Human Resource Quality, Discipline, and Motivation with job satisfaction and employee performance.